2022
DOI: 10.1039/d2dt00041e
|View full text |Cite
|
Sign up to set email alerts
|

New phthalonitrile/metal phthalocyanine–gold nanoparticle conjugates for biological applications

Abstract: The appearance of nanoscience and its effect on the development of the scientific fields particularly materials chemistry have been well-known today. In this study, a new di-substituted phthalonitrile derivative namely...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(53 citation statements)
references
References 78 publications
0
42
0
Order By: Relevance
“…In the mass spectra of compounds (2-Si, 3-Si, 2-QSi, and 3-QSi), molecular ion peaks were obtained at 1113. 32…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the mass spectra of compounds (2-Si, 3-Si, 2-QSi, and 3-QSi), molecular ion peaks were obtained at 1113. 32…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…26,27 The potent utility of phthalocyanines has been explored in the well-known scientific and technological fields that encompass electronics, sensing, medicine, and nanotechnology. [28][29][30][31][32][33][34][35][36][37] Since most of these applications require soluble materials, the insolubility of unsubstituted phthalocyanines in common organic and aqueous media is known as an essential limitation for their use in these fields. Introduction of bulky or long substituents on the periphery of phthalocyanines and insertion of metal cations into the phthalocyanine cavity increase the distance between the phthalocyanine rings and decrease the intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1–5 Previous investigations indicated that phthalocyanine and its derivatives can be widely used in various research fields, such as sonodynamic therapy (SDT), 6,7 industrial textile colorants, 8 molecular electronics materials and imaging, 9,10 optical limiters 11,12 and other various organic electronic devices. 13,14…”
Section: Introductionmentioning
confidence: 99%
“…Substituted metal phthalocyanine complexes and their gold nanoparticle and graphene conjugates have been known to exhibit antibacterial and photodynamic antibacterial activities. Representative precedents are mentioned here [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%